Pengembangan Produk Makanan Home Industry: Strategi Promosi dan Pemasaran Berbasis E-Commerce - Deqa Annisa G, Puti; Annas, Firdaus; Rahmadiani, Salfa (Yayasan Lembaga Studi Makwa, 2023)
This article aims to develop e-commerce-based promotional and marketing strategies for home industry food products in the Tanjung Raya District. Many home industry operators in this area have yet to fully utilize the available e-commerce platforms to promote their products. In fact, with the rapid advancement of technology, producers can now have significant opportunities to market their products to a broader audience, both locally and globally by using various available E-commerce platform that facilitate direct access and interaction with consumers. This research employs a Research and Development (R&D) approach, followed by the application of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model to design a web-based promotional solution. The outcome of this study is the creation of a web-based promotional medium using the OpenCart platform, which is expected to serve as an effective solution for marketing home industry food products. The research findings indicate that the use of OpenCart can enhance the visibility and appeal of food products produced by home industries in the Tanjung Raya District. This platform enables home industry operators to more easily reach potential consumers, facilitates online transactions, and optimizes promotional activities through digital media. It is anticipated that these findings will significantly contribute to the development of home industries, particularly in the food sector, and provide practical guidance for industry players in other regions seeking to leverage e-commerce to expand their markets.